2013
DOI: 10.4315/0362-028x.jfp-13-093
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation of Salmonella Serotypes in Simulated Meat Processing Environments and Its Relationship to Cell Characteristics

Abstract: Salmonella attached to meat contact surfaces encountered in meat processing facilities may serve as a source of cross-contamination. In this study, the influence of serotypes and media on biofilm formation of Salmonella was investigated in a simulated meat processing environment, and the relationships between biofilm formation and cell characteristics were also determined. All six serotypes (Salmonella enterica serotype Heidelberg, Salmonella Derby, Salmonella Agona, Salmonella Indiana, Salmonella Infantis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 26 publications
5
29
0
2
Order By: Relevance
“…3 and 4) suggested that the relative expression levels of the attachment genes (adrA, bapA, csgB, csgD and csrA) were influenced by the types of growth media, indicating that the mechanism of biofilm formation is somehow associated with the growth environment of the cells, a similar conclusion also drawn by others (Steenackers et al, 2012). The relatively low expression of attachments genes in biofilm cells as compared to planktonic cells at 3 days of incubation may result from the rudimentary phase of biofilm formation, when the attachment ability mainly results from the cells surface characteristics rather than EPS (Donlan, 2002), this phenomenon is also in line with our previous confocal laser scanning microscopy observations (Wang, Ding, Wang, Xu, & Zhou, 2013). The expression levels of csgB and csgD in TSB increased markedly by days 5 and 7 of incubation, in keeping with the development of a mature biofilm.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…3 and 4) suggested that the relative expression levels of the attachment genes (adrA, bapA, csgB, csgD and csrA) were influenced by the types of growth media, indicating that the mechanism of biofilm formation is somehow associated with the growth environment of the cells, a similar conclusion also drawn by others (Steenackers et al, 2012). The relatively low expression of attachments genes in biofilm cells as compared to planktonic cells at 3 days of incubation may result from the rudimentary phase of biofilm formation, when the attachment ability mainly results from the cells surface characteristics rather than EPS (Donlan, 2002), this phenomenon is also in line with our previous confocal laser scanning microscopy observations (Wang, Ding, Wang, Xu, & Zhou, 2013). The expression levels of csgB and csgD in TSB increased markedly by days 5 and 7 of incubation, in keeping with the development of a mature biofilm.…”
Section: Discussionsupporting
confidence: 89%
“…According to our previous study (Wang et al, 2013), the growth parameter values (T, (h), elapsed to stationary phase) in TSB and MTLB were 41 h and 56 h, respectively, the planktonic cells collected at 3 d, 5 d and 7 d in both growth media were in stationary phase, and the cell density were approximate 10 9 CFU/mL.…”
Section: Biofilm Formationmentioning
confidence: 86%
“…Salmonella causes gastroenteritis and in some cases septicaemia (Wang et al . ). Salmonella enterica is able to grow on stainless steel surfaces resulting in a 3D structure with several layers of cells, which may present different morphologies depending on the available nutrients (Wang et al .…”
Section: Inhibition Of Biofilm Formationmentioning
confidence: 97%
“…Salmonella remains an important cause of food-poisoning infections and has recently seen a resurgence in the EU primarily as a result of zoonotic infections (EFSA and ECDC 2017). Salmonella causes gastroenteritis and in some cases septicaemia (Wang et al 2013a). Salmonella enterica is able to grow on stainless steel surfaces resulting in a 3D structure with several layers of cells, which may present different morphologies depending on the available nutrients (Wang et al 2013b).…”
Section: Inhibition Of Biofilm Formationmentioning
confidence: 99%
“…Although much information on the control of planktonic Salmonella via various antimicrobial agents has been published, limited information is available on the control of biofilms in a poultry processing environment (8,18,28,30). The ability of Salmonella to form biofilms and quantification of biofilm formation on various surfaces consistent with food processing and storage have been documented (1,29). However, to our knowledge, there is no clear understanding of how to measure the sensitivity of biofilm and planktonic bacteria to specific disinfectants used during poultry processing.…”
mentioning
confidence: 99%